An Analysis of Higher Order Thinking Skills (HOTS) in the Implementation of Deep Learning Based Instruction through Joyful, Mindful, and Meaningful Learning - Al-Zahra, Shafinna (The Future of Education Journal, 2026)
The paradigm of 21st-century education emphasizes the importance of Higher-Order Thinking Skills (HOTS) as a fundamental foundation for addressing global challenges. This article analyzes the relationship between HOTS—encompassing analytical, critical, and creative thinking skills—and the deep learning curriculum concept that emphasizes joyful, mindful, and meaningful learning. The research method employs a literature review approach by examining scholarly articles published between 2024 and 2025 obtained from Google Scholar and nationally accredited reputable journals relevant to the development of HOTS within the context of the Merdeka Curriculum. The findings indicate that deep learning–based instruction is able to activate HOTS holistically: joyful learning stimulates creativity, mindful learning strengthens critical evaluation through metacognitive awareness, and meaningful learning facilitates in-depth analysis through contextual experiences. The integration of these three principles creates a humanistic and transformative learning ecosystem. This article affirms that a deep learning curriculum is not merely a pedagogical approach, but a strategic framework for improving the quality of national education based on 21st-century competencies.